when , arrange the following three expressions by magnitude :
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
a − 1 a = a − 1 a − 1 + 1 = a − 1 a − 1 + a − 1 1 = 1 + a − 1 1
a a + 1 = a a + a 1 = 1 + a 1
Since a > 1 , we know that
a 1 > 0 and a − 1 1 > 0
and
a − 1 < a ⟹ a − 1 1 > a 1
Therefore:
0 < a 1 < a − 1 1 ⟹ 1 < 1 + a 1 < 1 + a − 1 1 ⟹ 1 < a a + 1 < a − 1 a
Turn the inequality around, and we get the answer: a − 1 a > a a + 1 > 1